'All I got is stones in my hand': youth-led stone pelting protests in Indian-administered Kashmir. (2nd January 2021) - Ganie, Mohd Tahir
ABSTRACT: Since 2008, three anti-India mass uprisings occurred in Indian-administered Kashmir, resulting in a marked resurgence of the Kashmiri self-determination movement, known popularly as the Tehreek. In the resurgent Tehreek, stone-throwing – called kanni-jang in the local parlance, and stone pelting in the English language media – has emerged as a new and widely used act in the repertoire of Kashmiri resistance. The latest example of its use appeared after the Indian state's lockdown of Kashmir on 5 August 2019, when approximately 1193 stone-throwing protests were reported across Kashmir. For India, this protest tactic presents huge security challenges, yet for the Tehreek activists, stone pelting is an effective mode of protest that carries symbolic importance. In fact, the stone-throwing youth have become a signifier of the anti-India rebellion in post-2008 Kashmir. This article highlights the main factors that underlie the stone-throwing phenomenon in the Himalayan territory.